Currículo xeretado! Educação de Jovens e Adultos do Colégio Santa Cruz expressos no boletim Xerete!: 1983 - 2002 - Xavier, Sylvia (2015)
The objective is to analyze curricular conceptions of an educational institution in the Young Adults and Adults Education (EJA, Educação de Jovens e Adultos), between 1983 and 2002. The source for research is the serial material with dates produced by the EJA at Colégio Santa Cruz (EJACSC) in São Paulo, SP the Xerete! and is part of the lot collected in that course since 1974. Xerete! Is part of a reflection over the dynamics of the political and pedagogical project that makes proposals aiming at creativity, political awareness, and social action. Written by teachers, principals and coordinators, it reports, determines, analyzes, and evaluated practices focused in skills, values and attitudes that lead to widening the reflection horizons and the participation in the scholar world. The consistency of the EJA is validated in the dialog with national and international social and political movements, academic reflections and in students participation. The analysis intends to identify the pedagogical themes that comprise the Xeretes! Documents, and what is desired to be modified regarding the curriculum, what the authors propose, which impositions arise, and which tactics and strategies occur. Since the adult education program was established, in the 1970 s, pedagogical practice turned EJACSC into a place to refute the adult education program and the prescriptive curriculum. When considering it as a social place to recover cultural traditions and to stimulate ongoing studies for those who are economically and culturally marginalized, bricolage is constant